7OContrasting the drivers of response to immunotherapy across solid tumour types: Results from analysis of > 1000 cases. (7th November 2019) - Litchfield, K; Swanton, C; Turajlic, S; McGranahan, N; Quezada, S
Abstract: Background: Multiple genomic and transciptomic biomarkers have been associated with response to immune checkpoint inhibitor (CPI) therapy. Emerging evidence suggests that each solid tumour type has a unique mix of factors determining CPI response, reflecting the subtle differences in antigen repertoire and immune microenvironment across histologies. Compiling large-scale sequencing datasets of patients treated with CPI therapy, from a range of solid tumour types, allows detailed comparison of the contrasting immune drivers per histology. Understanding these differences enhances our understanding of the pathways influencing CPI response, which may be of utility for therapeutic and biomarker development. Methods: We compiled data from 13 CPI treated cohorts, across 6 solid tumour types, encompassing 1, 453 patients (n = 1, 453 with exome data, n = 674 with RNAseq data). All raw data was accessed, and reprocessed through a standardised state of the art bioinformatics pipeline. A comphrehensive range of genomic & transcriptomic biomarker metrics were derived across the cohort. A combined predictive model was constructred encompassing all biomarkers, & the importance weighting was calculated for each biomarker, in each tumour type. Results: TMB was found to be a universal predictor of response across all tumour types, except for renal cell carcinoma (RCC). Instead CPI response in RCC appears to be strongly driven by expression of human endogeneuos retroviruses (hERV). In malignant melanoma, while TMB (nsSNVs) was associated with CPI response, the number of expressed indel mutations was found to be a stronger predictor. Shared antigen expression also demonstrated tumour specific predictive patterns. A signature of high immune inflitatation was found to be another universal predictor of response across multiple tumour types, however differences in the varying importance of immune cell subsets across histologies was observed. The rate of HLA LOH, and other immune evasion mechanisms also varied dramatically by cancer type. Conclusions: The determinants of immunotherapy response vary across solid tumour types, offering unique insight into both tumour intrinsic and extrinsic drivers of immunogenicity. Legal entity responsible for the study: The Francis Crick Institute. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.